2019
DOI: 10.5935/0103-507x.20190005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bronchial hygiene techniques in mechanically ventilated patients: a randomized clinical trial

Abstract: Objective To compare the effects of vibrocompression and hyperinflation with mechanical ventilator techniques alone and in combination (hyperinflation with mechanical ventilator + vibrocompression) on the amount of aspirated secretion and the change in hemodynamic and pulmonary parameters. Methods A randomized clinical trial with critically ill patients on mechanical ventilation conducted in the intensive care unit of a university hospital. The patients were randomly al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Regarding the safety of the maneuvers, 5 these were repeated in 4-5 consecutive cycles, which seemed not to cause adverse effects, such as hemodynamic instability, patient discomfort, or increased airway resistance. This corroborates the studies by Sarmento et al 13 and Naue et al, 15 who compared different bronchial hygiene techniques, combined and isolated, and concluded that the techniques were safe and that, when combined, they appeared to be more efficient in reducing the frequency of aspiration and the duration of mechanical ventilation.…”
supporting
confidence: 90%
“…Regarding the safety of the maneuvers, 5 these were repeated in 4-5 consecutive cycles, which seemed not to cause adverse effects, such as hemodynamic instability, patient discomfort, or increased airway resistance. This corroborates the studies by Sarmento et al 13 and Naue et al, 15 who compared different bronchial hygiene techniques, combined and isolated, and concluded that the techniques were safe and that, when combined, they appeared to be more efficient in reducing the frequency of aspiration and the duration of mechanical ventilation.…”
supporting
confidence: 90%
“…We included nine studies that compared manual hyperinflation with usual care, two randomized crossover trial (Choi & Jones, 2005; Hodgson et al., 2000) and seven randomized controlled trial (Barker & Adams, 2002; Blattner et al., 2008; Maa et al., 2005; Malekzadeh et al., 2016; Patman et al., 2000, 2009; Paulus et al., 2011; Table 1). There were four studies comparing hyperinflation performed using the mechanical ventilator with usual care, three randomized crossover trial (Assmann et al., 2016; Chicayban, 2019; Lemes et al., 2009) and one randomized controlled trial (Naue et al., 2019; Table 2). Four more studies that compared that compared manual hyperinflation with that performed using the mechanical ventilator, with three randomized crossover trials (Berney & Denehy, 2002; Dennis et al., 2012; Savian et al., 2006) and one randomized controlled trial (Ahmed et al., 2010; Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…According to the PEDro scale, 10 studies were classified as of high methodological quality (Assmann et al., 2016; Blattner et al., 2008; Chicayban, 2019; Choi & Jones, 2005; Hodgson et al., 2000; Lemes et al., 2009; Naue et al., 2019; Patman et al., 2000, 2009; Paulus et al., 2011) and seven of moderate quality (Ahmed et al., 2010; Barker & Adams, 2002; Berney & Denehy, 2002; Dennis et al., 2012; Maa et al., 2005; Malekzadeh et al., 2016; Savian et al., 2006). As noted, most of the selected studies were classified as of high methodological quality (PEDro scale > 5 points).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations